Singing reconciliation: inhabiting the moral life according to Colossians 3:16 - Krall, Amy Whisenand ca. 21. Jhd. (Biblical interpretation series, 2023)
"The letter to the Colossians contains a series of moral instructions in Colossians 3:12-17 and includes the admonition to "sing" among them. This study considers how music-making (specifically singing) supports moral formation according to the letter to the Colossians. Studies in ethnomusicology, anthropology of the voice, and music psychology offer useful frameworks for conceptualizing how a social practice like music-making forms participants into a community and shapes how they know themselves, their community, and the world. With the aid of these frameworks, we find that the singing in Colossians 3:16, as a corporate, vocal practice of music-making, enables the members of the church community to inhabit the story of reconciliation found in the Christ Hymn (Col 1:15-20)"-- Provided by publisher